Teacher Perception of Student Interest in Multicultural Tradebooks - Lambert, Judy C. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
This study investigated elementary school teachers' perception of their first grade students' interest in multicultural trade books. The study participants included 151 first graders, 17 experienced teachers, and 65 preservice teachers. The study used 15 multicultural trade books and 15 non-multicultural books matched as closely as possible in overall size and visual appeal. Children were shown the 30 books and then asked to indicate their interest in each. Teachers were also asked to rate their interest in each book. Findings indicated that amount of diversity within the school had an effect on children's interest in the two types of books. Children in heterogeneous classrooms rated the non-multicultural books significantly higher than the multicultural books. Children in homogenous classrooms did not rate the books significantly differently. Experienced teachers in heterogeneous classrooms and preservice teachers indicated that children would like the non-multicultural books more. Experienced teachers in homogenous classrooms did not perceive that the children would rate the books differently. It was also found that the same books do not appeal to both boys and girls, and that teachers in general are more accurate in their perception of girls' interest than they are of boys'. (Contains 14 references.) (JB)
ERIC Note: Paper presented at the Annual Meeting of the Midwestern Educational Research Association (Chicago, IL, October 1994).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Books; Childrens Literature; Cultural Pluralism; Elementary School Students; Elementary School Teachers; Grade 1.; Heterogeneous Grouping; Homogeneous Grouping; Primary Education; Reading Instruction; Reading Interests; Sex Differences; Student Attitudes; Student Teachers; Teacher Attitudes; Teaching Experience; Multicultural Materials; Diversity (Student); Reports, Research; Speeches/Meeting Papers